Normal Transformations for Overhang Reduction - Castro, Carlos Leal de; Sacht, Leonardo Koller (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2019)
We present a partial solution for the problem of reducing overhanging parts of a surface to 3D print it with minimal number of supports. We first present a summary about how a 3D printer works and why the overhanging problem happens. This review focuses on a specific type of 3D printer that uses polymer melted to print solids on cross-sectional layers. We then do a fast review of three-dimensional surface representation in a computer and its discrete representation. Then we present our minimization problem and show some test results, using libigl library and gptoolbox functions, to observe the solution of problem.